Current Epidemiological Assessment of Bancroftian Filariasis in Tanga Region, Northeastern Tanzania. (6th December 2016) - Mshana, Happyness J.; Baraka, Vito; Misinzo, Gerald; Makunde, Williams H.
Abstract : Background . Tanzania started a countrywide lymphatic filariasis elimination programme in 2000 adopting the mass drug administration (MDA) strategy. The drug used for the programme was the combination of ivermectin and albendazole. However, there is limited information on the current epidemiological trend of the infections, where MDA implementation is ongoing. The present study aimed at assessing the current status of Bancroftian filariasis infection rate and morbidity where MDA has been distributed and administered for over eight rounds. Methodology . The study was a cross-sectional descriptive study involving 272 individuals (>18 years) from endemic communities in Tanga region where MDA has been implemented. Clinical, sociodemographic, and circulating filarial antigen (CFA) test was undertaken using immune chromatographic card test according to the manufacturer's instructions. Results . A total of 472 individuals were screened: 307/472 (65.1%) were males while 165/472 (34.9%) were females. The overall prevalence of CFA was 5.51%, that of hydrocoele was 73.2%, and that of lymphoedema was 16.0%. The prevalence of hydrocoele combined with lymphoedema was 5.5%. Conclusion . Our findings demonstrate a considerable reduction in filarial infection. However, there is clear evidence of ongoing transmission despite the 8 rounds of MDA. It is unlikely that the annual MDA would interrupt filarial transmission; therefore, additional strategies are needed to accelerate lymphatic filariasis control and elimination.